Vanadosilicate with MWW zeolite structure synthesized from VCl3 by cooperative assembly of organic templates - Chaves, Thiago F. [UNESP]; Passos, Aline R.; Briois, Valérie; Martins, Leandro [UNESP]; Pulcinelli, Sandra H. [UNESP]; Santilli, Celso V. [UNESP]; Pérez-Pariente, Joaquín (Elsevier, 2019)
Aluminum-free MWW structure containing vanadium was easily prepared from a mixture of suitable templates (N,N,N-trimethyl-1-adamantamonium hydroxide (TMAdaOH) and hexamethyleneimine (HMI)). Besides, the use of VCl3 as vanadium source, in which this metal is in low oxidation state (V3+) and the preparation of the synthesis gel under inert atmosphere are crucial to get an efficient incorporation of vanadium into the zeolitic framework. UV–Vis spectrum of the as-synthesized material whose oxidation was prevented by working under inert atmosphere reveals the presence of isolated V3+ sites isomorphically coordinated. Besides, the 29Si MAS NMR spectra and the V K-edge X-ray Absorption Spectroscopy (XAS) analysis show that the vanadium was incorporated into the zeolite framework with formation of V–O–Si linkages. 13C MAS NMR evidences that both templates are present in the as-synthesized material, showing that the mixture of TMAdaOH and HMI is crucial for obtaining pure crystalline vanadosilicate phase. XAS measurements of the V-containing zeolite during calcination under air showed that initially the sample contains V4+ sites in a square pyramidal geometry, which were completely oxidized to isolated V5+ in Td coordination after calcination.
Keywords: Mixed templates; MWW; V3+ and V4+; Vanadosilicate